2018
DOI: 10.1080/17515831.2018.1558026
|View full text |Cite
|
Sign up to set email alerts
|

A friction and wear study of laboratory aged engine oil in the presence of diesel fuel and oxymethylene ether

Abstract: Non-fossil fuels for the commercial and passenger vehicle sector are gaining more importance due to their positive effects on exhaust gas emissions. Ongoing research investigating a broad variety of biofuels, synthetic fuels and regenerative fuels shows that a reduction of CO 2 emissions can be possible without major modifications to the existing vehicle infrastructure. An internal combustion engine is a complex system of physical and chemical mechanisms, all of which contribute to the performance output, exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Research [22] confirms that ethanol generally increases wear while having a minimal impact on the aging performance of lubricant oil [23]. Therefore, it could be concluded that conventional fuel modification by adding alternative fuels results in dilution and degradation of engine oil, which affect thermodynamic efficiency as well as friction [24] and increased wear in the contact pairs and bearing surfaces of an IC engine [1].…”
Section: Introductionmentioning
confidence: 75%
“…Research [22] confirms that ethanol generally increases wear while having a minimal impact on the aging performance of lubricant oil [23]. Therefore, it could be concluded that conventional fuel modification by adding alternative fuels results in dilution and degradation of engine oil, which affect thermodynamic efficiency as well as friction [24] and increased wear in the contact pairs and bearing surfaces of an IC engine [1].…”
Section: Introductionmentioning
confidence: 75%
“…The development of this technique was based on the performed works related to the classical methods of experimental friction research [54,56,60,64,78,79]. To deal with the tasks, a systematic approach was used in wear resistance tests.…”
Section: Methodsmentioning
confidence: 99%
“…These indicators can have a positive effect on the service life of a diesel engine. However, there are disadvantages that need to be addressed: biodiesel increases the chemical wear of diesel engine parts because it is more aggressive than conventional diesel fuel [60][61][62][63][64][65].…”
Section: Biodiesel (3rd Generation)mentioning
confidence: 99%
“…However, in this case, a problem arises, which lies in the poor tribological properties of these light metals as well as in the lower strength compared to the cast iron construction. A similar approach was taken by Mosarof et al (2016) [31] and Nag et al (2019) [32], who proposed improving the tribological properties of cylinder liners and increased the mechanical efficiency of the engine when using biodiesel fuel through a thermal spray process and high-velocity oxyfuel coatings, the use of various nano-additives, and the addition of bioethanol to diesel-biodiesel mixtures. However, in all such works, there was no methodology for a comprehensive assessment of the reliability of fuel systems, thanks to which it is possible to compare the effectiveness of increasing the resource of internal combustion engines.…”
Section: Introductionmentioning
confidence: 93%